BILINGUALISME DALAM PEMBELAJARAN BAHASA ARAB - Windasari, Ririn (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2020)
Bilingualism or language dualism in learning Arabic is something that is often found in Indonesia, even in all countries in the process of learning foreign languages for native speakers. The use of two languages (bilingualism) in foreign language learning aims to provide understanding to foreign language learners, because they are accustomed to using the original language along with the types of words and sentence structure, so the need for native language interventions of speakers in learning foreign languages. The level of ability of students varies according to their level, therefore clear explanations are needed through the learner's native language as an intermediary language.